2016
DOI: 10.1108/ijchm-12-2014-0611
|View full text |Cite
|
Sign up to set email alerts
|

Social entrepreneurs: innovating rural tourism through the activism of service science

Abstract: Purpose This study aims to construct an integrated social entrepreneur system in the rural area of Hengshan, Taiwan, that could benefit four stakeholders, namely, tourists, business, community and government. Two social entrepreneur cases demonstrate a mutually beneficial situation of lowering the structural unemployment rate, returning young human capital to villages and innovating rural tourism through the activism of service science. Design/methodology/approach Qualitative approach was applied to data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
0
42
0
1
Order By: Relevance
“…A tourism social enterprise ("socent"), such as a home-stay operation, which is a non-traditional economic activity for communities in geographically-remote or peripheral regions, provides both benefits and challenges [119][120][121][122][123]. Human resources management prevails as a core issue for communities delivering tourism services and the National Tourism Organizations (NTOs) that are responsible for managing tourists' expectations [124].…”
Section: Tourism Social Enterprise and Sustainable Human Resource Manmentioning
confidence: 99%
“…A tourism social enterprise ("socent"), such as a home-stay operation, which is a non-traditional economic activity for communities in geographically-remote or peripheral regions, provides both benefits and challenges [119][120][121][122][123]. Human resources management prevails as a core issue for communities delivering tourism services and the National Tourism Organizations (NTOs) that are responsible for managing tourists' expectations [124].…”
Section: Tourism Social Enterprise and Sustainable Human Resource Manmentioning
confidence: 99%
“…Departing from a general absence of adequate innovation statistics in tourism (Hjalager, 2010) that would allow to capture highly diversified set of new niche services enhanced by web platforms we apply case study approach, used regularly in the research of tourism innovation (Liburd and Hjalager, 2010;Peng & Lin, 2016) and hospitality (Singh, 2011;Strobl and Kronenberg, 2016). It is observed that when it comes to innovation cooperation between the actors there is a need for in-depth case studies focusing on the characteristics of successful innovation partnerships, their emergence, management and sustainability (Larson, 2009).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Hicks proposed a model for implementing knowledge management composed of the four following stages: creating, storing, distributing, and implementing knowledge (Peng and Lin, 2016).…”
Section: Knowledge Management Processesmentioning
confidence: 99%